Genome-wide study for circulating metabolites identifies 62 loci and reveals novel systemic effects of LPA - Kettunen, Johannes; Demirkan, Ayşe; Würtz, Peter; Draisma, Harmen H.M.; Haller, Toomas; Rawal, Rajesh; Vaarhorst, Anika; Kangas, Antti J.; Lyytikäinen, Leo-Pekka; Pirinen, Matti; Pool, René; Sarin, Antti-Pekka; et al. (Nature communications, 2016)
Genome-wide association studies have identified numerous loci linked with complex diseases, for which the molecular mechanisms remain largely unclear. Comprehensive molecular profiling of circulating metabolites captures highly heritable traits, which can help to uncover metabolic pathophysiology underlying established disease variants. We conduct an extended genome-wide association study of genetic influences on 123 circulating metabolic traits quantified by nuclear magnetic resonance metabolomics from up to 24,925 individuals and identify eight novel loci for amino acids, pyruvate and fatty acids. The LPA locus link with cardiovascular risk exemplifies how detailed metabolic profiling may inform underlying aetiology via extensive associations with very-low-density lipoprotein and triglyceride metabolism. Genetic fine mapping and Mendelian randomization uncover wide-spread causal effects of lipoprotein(a) on overall lipoprotein metabolism and we assess potential pleiotropic consequences of genetically elevated lipoprotein(a) on diverse morbidities via electronic health-care records. Our findings strengthen the argument for safe LPA -targeted intervention to reduce cardiovascular risk. Circulating metabolites reflect human health and disease. Here, Kettunen et al . perform a genome-wide association study on 123 circulating metabolic traits and identify novel genetic loci influencing systemic metabolism. They also link new molecular pathways with a known cardiovascular risk factor Lp(a).